SAFETY PROFILE OF PRE-WORKOUT SUPPLEMENTS AND ENERGY DRINKS IN AMATEUR SPORTS: A NARRATIVE REVIEW OF CARDIOVASCULAR AND NEUROPSYCHIATRIC RISKS - Michał Napierała; Aleksandra Zimnoch-Włodarczyk; Maciej Łapiński; Oksana Zinko; Kinga Ciecierska; Krystyna Wasilkowska; Sylwia Łatkowska (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: The consumption of multi-ingredient pre-workout supplements (MIPS) and energy drinks has become ubiquitous in amateur sports. While these products promise enhanced performance and focus, they often contain high doses of stimulants and proprietary blends that pose significant health risks when used without medical supervision. Aim: The aim of this narrative review is to analyze the safety profile of pre-workout supplements and energy drinks, specifically focusing on cardiovascular, neuropsychiatric, and metabolic risks associated with their acute and chronic consumption. Material and methods: A narrative review of current literature was conducted using PubMed, Google Scholar, and Web of Science databases. The analysis focused on original papers, systematic reviews, and case reports regarding caffeine intoxication, MIPS safety, and adverse events in athletes. Results: Epidemiological data indicates that over 50% of regular pre-workout users experience side effects such as tachycardia, palpitations, and nausea. High-risk behaviors, such as consuming multiple servings ("double scooping"), significantly increase the risk of adverse cardiovascular events. While moderate caffeine intake (e.g., coffee) appears safe for young athletes, the supraphysiological doses found in supplements can lead to severe toxicity, anxiety, and sleep disturbances. Furthermore, fatal cases of caffeine intoxication confirm the lethal potential of unsupervised supplementation. Conclusions: Education regarding the risks of "stacking" supplements and exceeding recommended doses is critical. Athletes should be encouraged to use safer, natural alternatives and prioritize sleep and nutrition over pharmacological stimulation.